Partisipasi Publik dalam Penyusunan Undang-Undang: Mendorong Keterlibatan Masyarakat dalam Pembentukan Kebijakan - Cahyo Danang Prayugo; Yuli Agung Nugroho; Burhanudin Ahmad; Muhammad Bondhi Alby; Diaz Kartika Aprillio; Fanny Dian Saputra; Kuswan Hadji (UNIVERSITAS SERAMBI MEKKAH, 2024)
Public participation in the process of drafting laws is a key element in maintaining the quality of a country's democracy. In an era of ever-developing social, economic and political dynamics, community participation is becoming increasingly important to ensure that the resulting policies reflect the needs and aspirations of society at large. Nevertheless, challenges in public participation in the legislative process are still things that need to be overcome. In the current digital era, advances in information and communication technology open up new opportunities to increase public participation in drafting laws. However, gaps in access and digital literacy are still obstacles that need to be overcome. Internal factors in the political and legal system can also hinder effective public participation, such as complex bureaucratic structures, lack of transparency in the legislative process, and limited accessibility of information. At the global level, the trend of increasing public participation in policy formation is a major concern, with various initiatives launched to increase public involvement. In Indonesia, public participation in the legislative process is increasingly important along with the development of democracy. This article discusses the importance of public participation in drafting laws, the challenges faced, and strategies to encourage community involvement in policy formation. With collaboration between government, legislative institutions, civil society and the private sector, it is hoped that an environment that supports effective public participation can be created. The goal is to create policies that are inclusive and responsive to the needs of society as a whole.